Complete genome sequence of citrus tristeza virus isolate PB61, a commercially deployed mild strain for cross-protection in grapefruit - M. A. Jackson; D. B. Kidanemariam; G. A. Chambers; A. Englezou; A. D.W. Geering; N. J. Donovan (Australasian Plant Pathology, 2026)
Citrus tristeza virus (CTV; species Closterovirus tristezae ) is ubiquitous in Australia, occurring in all production areas. Stem-pitting disease in white grapefruit varieties caused by CTV is managed by mild strain cross-protection. However, the protective isolate of CTV used for cross-protection, labelled PB61, is not fully characterised at the molecular level, even though most grapefruit budwood is inoculated with this virus isolate before release. In this study, we employed high throughput sequencing to assemble the 19,254 nucleotide-long genome of virus isolate PB61. Phylogenetic analysis revealed that PB61 belongs to the resistance-breaking (RB) genotype group first identified in New Zealand. PB61 is the first CTV isolate of any genotype from Australia to be sequenced in entirety, and the generation of this data provides a foundation for better understanding the mechanism of cross-protection in grapefruit.

Endocrine Disrupting Chemicals in Human Milk: A Systematic Review of Concentrations and Potential Health Implications - Fiona Dunn; Hannah Sullivan; Megan Romano; Christina D. Chambers; Joseph M. Braun; Katherine E. Manz (Current Environmental Health Reports, 2025)
Purpose of Review Endocrine-disrupting chemicals (EDCs) disrupt the synthesis, transport, action, or metabolism of endogenous hormones in the human body. EDCs often enter the body through inhalation, ingestion, or dermal contact and can accumulate in the body. Remobilization or transfer of EDCs can occur during lactation, causing human milk to become contaminated with a variety of EDCs, which could expose nursing infants and children to these chemicals. Recent Findings Several studies have examined the concentration ranges for one or multiple EDC(s) in human milk. Additional studies document associations between EDC exposure and adverse health outcomes, many of which are in adult populations. It is therefore essential to understand the extent to which EDCs in human milk contribute to cumulative early-life exposures. Summary We performed a literature review of peer-reviewed studies reporting concentrations of one or more of the following EDCs in human milk during or after 2004: bisphenols, organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs), parabens, polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), per- and polyfluoroalkyl substances (PFAS), and phthalates. We identified concentration ranges for each chemical detected in human milk and health impacts associated with early-life exposures to EDCs noted across studies from this review. Determining the presence of EDCs in human milk and the associated effects of exposure through nursing is essential to develop feeding recommendations that safeguard infant and child health.

Litter production and foliar nutrient resorption in fast- and slow-growing tree species in the Central Amazon - Luciane de L. Carvalho; Bruno O. Gimenez; Barbara Bomfim; Jeffrey Q. Chambers; Savanah F. de Freitas; Daisy C. Souza; Charles D. Koven; Cacilda Adélia S. de Souza; Nate McDowell; Adriano José N. Lima; Niro Higuchi (Forest Ecology and Management, 2025)

P30-52 TempO-LINC single-cell transcriptomics assay sensitively resolves cellular heterogeneity and elucidates mechanisms of toxicity - S. Camiolo; D. Eastburn; K. White; N. Jayne; D. Gallegos; B. Robinette; B. Chambers; M. Campbell; S. Martos; D. Bell; B. Chorley; I. Shah; et al. (Toxicology Letters, 2025)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

High-Throughput Transcriptomics Screen of ToxCast Chemicals in U-2 OS Cells - Joseph L. Bundy; Logan J. Everett; Jesse D. Rogers; Jo Nyffeler; Gabrielle Byrd; Megan Culbreth; Derik E. Haggard; Laura J. Word; Bryant A. Chambers; Sarah Davidson-Fritz; Felix Harris; Clinton Willis; et al. (Toxicology and Applied Pharmacology, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Mid-season nitrogen management for winter wheat under price and weather uncertainty - Xiangjie Chen; Robert G. Chambers; Varaprasad Bandaru; Curtis D. Jones; Tyson E. Ochsner; Rohit Nandan; Bharath C. Irigireddy; Romulo P. Lollato; Travis W. Witt; Charles W. Rice (Field Crops Research, 2024)

Hysteresis area at the canopy level during and after a drought event in the Central Amazon - Bruno O. Gimenez; Daisy C. Souza; Niro Higuchi; Robinson I. Negrón-Juárez; Israel de Jesus Sampaio-Filho; Alessandro C. Araújo; Adriano J.N. Lima; Clarissa G. Fontes; Kolby J. Jardine; Charles D. Koven; Lin Meng; Gilberto Pastorello; et al. (Agricultural and Forest Meteorology, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Beach litter sources around Nuuk, Greenland: An analysis by UArctic summer school graduate course students - Marthe Larsen Haarr; Lis Bach; Catherine P. Chambers; Jannike Falk-Andersson; Thomas Juul-Pedersen; Ryan d'Arcy Metcalfe; Anna Sinisalo; Jakob Strand; Helene Svendsen; Julia E. Baak; Helga Hvanndal Björnsdóttir; Elsa Margaret Krook Brenner; et al. (Marine Pollution Bulletin, 2023)

Investigating the vertical and spatial extent of radon-based classification of the atmospheric mixing state and impacts on seasonal urban air quality - Dafina Kikaj; Scott D. Chambers; Jagoda Crawford; Matjaž Kobal; Asta Gregorič; Janja Vaupotič (Science of The Total Environment, 2023)

Assessing the impact of synoptic weather systems on air quality in Sydney using Radon 222 - Jagoda Crawford; Scott D. Chambers; Alastair G. Williams (Atmospheric Environment, 2023)

Atmospheric concentrations and sources of black carbon over tropical Australian waters - Changda Wu; Haydn Trounce; Erin Dunne; David W.T. Griffith; Scott D. Chambers; Alastair G. Williams; Ruhi S. Humphries; Luke T. Cravigan; Branka Miljevic; Chunlin Zhang; Hao Wang; Boguang Wang; et al. (Science of The Total Environment, 2023)

Diagnostic KASP markers differentiate Vanilla planifolia, V. odorata, V. pompona, and their hybrids using leaf or cured pod tissues - Joshua D. Anderson; Manuel Gastelbondo; Alan H. Chambers (Molecular Biology Reports, 2023)

Genotyping-by-sequencing of passion fruit (Passiflora spp.) generates genomic resources for breeding and systematics - Joshua D. Anderson; Ravena Ferreira Vidal; Maria Brym; Eric T. Stafne; Marcio F. R. Resende; Alexandre Pio Viana; Alan H. Chambers (Genetic Resources and Crop Evolution, 2022)

White matter tract conductivity is resistant to wide variations in paranodal structure and myelin thickness accompanying the loss of Tyro3: an experimental and simulated analysis - Farrah Blades; Jordan D. Chambers; Timothy D. Aumann; Christine T. O. Nguyen; Vickie H. Y. Wong; Andrea Aprico; Eze C. Nwoke; Bang V. Bui; David B. Grayden; Trevor J. Kilpatrick; Michele D. Binder (Brain Structure and Function, 2022)

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Combined selective culture and molecular methods for the detection of carbapenem-resistant organisms from fecal specimens - Rebecca Yee; Stefanie Fisher; Yehudit Bergman; Krizia K. Chambers; Pranita D. Tamma; Karen C. Carroll; Patricia J. Simner (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Quantifying the contribution of matric suction on changes in stability and displacement rate of a translational landslide in glaciolacustrine clay - K. Sattler; D. Elwood; M. T. Hendry; D. Huntley; J. Holmes; P. B. Wilkinson; J. Chambers; S. Donohue; P. I. Meldrum; R. Macciotta; P. T. Bobrowsky (Landslides, 2021)

Forest responses to simulated elevated CO 2 under alternate hypotheses of size‐ and age‐dependent mortality - Jessica F. Needham; Jeffrey Chambers; Rosie Fisher; Ryan Knox; Charles D. Koven (Global Change Biology, 2020)
Elevated atmospheric carbon dioxide (eCO 2 ) is predicted to increase growth rates of forest trees. The extent to which increased growth translates to changes in biomass is dependent on the turnover time of the carbon, and thus tree mortality rates. Size‐ or age‐dependent mortality combined with increased growth rates could result in either decreased carbon turnover from a speeding up of tree life cycles, or increased biomass from trees reaching larger sizes, respectively. However, most vegetation models currently lack any representation of size‐ or age‐dependent mortality and the effect of eCO 2 on changes in biomass and carbon turnover times is thus a major source of uncertainty in predictions of future vegetation dynamics. Using a reduced‐complexity form of the vegetation demographic model the Functionally Assembled Terrestrial Ecosystem Simulator to simulate an idealised tropical forest, we find increases in biomass despite reductions in carbon turnover time in both size‐ and age‐dependent mortality scenarios in response to a hypothetical eCO 2 ‐driven 25% increase in woody net primary productivity (wNPP). Carbon turnover times decreased by 9.6% in size‐dependent mortality scenarios due to a speeding up of tree life cycles, but also by 2.0% when mortality was age‐dependent, as larger crowns led to increased light competition. Increases in aboveground biomass (AGB) were much larger when mortality was age‐dependent (24.3%) compared with size‐dependent (13.4%) as trees reached larger sizes before death. In simulations with a constant background mortality rate, carbon turnover time decreased by 2.1% and AGB increased by 24.0%, however, absolute values of AGB and carbon turnover were higher than in either size‐ or age‐dependent mortality scenario. The extent to which AGB increases and carbon turnover decreases will thus depend on the mechanisms of large tree mortality: if increased size itself results in elevated mortality rates, then this could reduce by about half the increase in AGB relative to the increase in wNPP.

Application of multi-dimensional electrical resistivity tomography datasets to investigate a very slow-moving landslide near Ashcroft, British Columbia, Canada - D. Huntley; P. Bobrowsky; M. Hendry; R. Macciotta; D. Elwood; K. Sattler; M. Best; J. Chambers; P. Meldrum (Landslides, 2019)

Rheological properties of clayey soils originating from flow-like landslides - S. R. Carrière; D. Jongmans; G. Chambon; G. Bièvre; B. Lanson; L. Bertello; M. Berti; M. Jaboyedoff; J.-P. Malet; J. E. Chambers (Landslides, 2018)

Plants in aquatic ecosystems: current trends and future directions - Matthew T. O’Hare; Francisca C. Aguiar; Takashi Asaeda; Elisabeth S. Bakker; Patricia A. Chambers; John S. Clayton; Arnaud Elger; Teresa M. Ferreira; Elisabeth M. Gross; Iain D. M. Gunn; Angela M. Gurnell; Seppo Hellsten; et al. (Hydrobiologia, 2018)

Experiments with By-Catch Reduction Devices to Exclude Diamondback Terrapins and Retain Blue Crabs - Andrew D. Corso; Jacqueline C. Huettenmoser; Olivia R. Trani; Kory Angstadt; Donna Marie Bilkovic; Kirk J. Havens; Timothy M. Russell; David Stanhope; Randolph M. Chambers (Estuaries and Coasts, 2017)

Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana - Emily M. Saad; Amelia F. Longo; Luke R. Chambers; Rixiang Huang; Claudia Benitez‐Nelson; Sonya T. Dyhrman; Julia M. Diaz; Yuanzhi Tang; Ellery D. Ingall (Limnology and Oceanography, 2016)

3D ground model development for an active landslide in Lias mudrocks using geophysical, remote sensing and geotechnical methods - A. J. Merritt; J. E. Chambers; W. Murphy; P. B. Wilkinson; L. J. West; D. A. Gunn; P. I. Meldrum; M. Kirkham; N. Dixon (Landslides, 2014)

Consistency of the current global ocean observing systems from an Argo perspective - K. von Schuckmann; J.-B. Sallée; D. Chambers; P.-Y. Le Traon; C. Cabanes; F. Gaillard; S. Speich; M. Hamon (Ocean Science, 2014)
Variations in the world's ocean heat storage and its associated volume changes are a key factor to gauge global warming and to assess the earth's energy and sea level budget. Estimating global ocean heat content (GOHC) and global steric sea level (GSSL) with temperature/salinity data from the Argo network reveals a positive change of 0.5 ± 0.1 W m−2 (applied to the surface area of the ocean) and 0.5 ± 0.1 mm year−1 during the years 2005 to 2012, averaged between 60° S and 60° N and the 10–1500 m depth layer. In this study, we present an intercomparison of three global ocean observing systems: the Argo network, satellite gravimetry from GRACE and satellite altimetry. Their consistency is investigated from an Argo perspective at global and regional scales during the period 2005–2010. Although we can close the recent global ocean sea level budget within uncertainties, sampling inconsistencies need to be corrected for an accurate global budget due to systematic biases in GOHC and GSSL in the Tropical Ocean. Our findings show that the area around the Tropical Asian Archipelago (TAA) is important to closing the global sea level budget on interannual to decadal timescales, pointing out that the steric estimate from Argo is biased low, as the current mapping methods are insufficient to recover the steric signal in the TAA region. Both the large regional variability and the uncertainties in the current observing system prevent us from extracting indirect information regarding deep-ocean changes. This emphasizes the importance of continuing sustained effort in measuring the deep ocean from ship platforms and by beginning a much needed automated deep-Argo network.

Laugh yourself to sleep: memory consolidation for humorous information - Alexis M. Chambers; Jessica D. Payne (Experimental Brain Research, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Brachypodium distachyon Cell Suspension Cultures: Establishment and Utilisation - D. Hunt; J.P. Chambers; A. Behpouri; S.P. Kelly; L. Whelan; M. Pietrzykowska; F. Downey; P.F. McCabe; C.K.-Y. Ng (Cereal Research Communications, 2014)

Long-term ecological study (palaeoecology) to chronicle habitat degradation and inform conservation ecology: an exemplar from the Brecon Beacons, South Wales - F. M. Chambers; E. W. Cloutman; J. R. G. Daniell; D. Mauquoy; P. S. Jones (Biodiversity and Conservation, 2013)

Evaluation of Release-05 GRACE time-variable gravity coefficients over the ocean - D. P. Chambers; J. A. Bonin (Ocean Science, 2012)
The latest release of GRACE (Gravity Recovery and Climate Experiment) gravity field coefficients (Release-05, or RL05) are evaluated for ocean applications. Data have been processed using the current methodology for Release-04 (RL04) coefficients, and have been compared to output from two different ocean models. Results indicate that RL05 data from the three Science Data Centers – the Center for Space Research (CSR), GeoForschungsZentrum (GFZ), and Jet Propulsion Laboratory (JPL) – are more consistent among themselves than the previous RL04 data. Moreover, the variance of residuals with the output of an ocean model is 50–60% lower for RL05 data than for RL04 data. A more optimized destriping algorithm is also tested, which improves the results slightly. By comparing the GRACE maps with two different ocean models, we can better estimate the uncertainty in the RL05 maps. We find the standard error to be about 1 cm (equivalent water thickness) in the low- and mid-latitudes, and between 1.5 and 2 cm in the polar and subpolar oceans, which is comparable to estimated uncertainty for the output from the ocean models.

Factors associated with diagnostic and treatment intervals for prostate cancer in Queensland, Australia: a large cohort study - Peter D. Baade; Robert A. Gardiner; Megan Ferguson; Danny R. Youlden; Joanne F. Aitken; John Yaxley; Suzanne K. Chambers (Cancer Causes & Control, 2012)

Mouse transmembrane BAX inhibitor Motif 3 (Tmbim3) encodes a 38 kDa transmembrane protein expressed in the central nervous system - Joseph A. Nielsen; Meredith A. Chambers; Elena Romm; Laurel Yong-Hwa Lee; Jo Ann Berndt; Lynn D. Hudson (Molecular and Cellular Biochemistry, 2011)

ENSO-correlated fluctuations in ocean bottom pressure and wind-stress curl in the North Pacific - D. P. Chambers (Ocean Science, 2011)
We examine the output of an ocean model forced by ECMWF winds to study the theoretical relationship between wind-induced changes in ocean bottom pressure in the North Pacific between 1992 until 2010 and ENSO. Our analysis indicates that while there are significant fluctuations correlated with some El Niño and La Niña events, the correlation is still relatively low. Moreover, the ENSO-correlated variability explains only 50 % of the non-seasonal, low-frequency variance. There are significant residual fluctuations in both wind-stress curl and ocean bottom pressure in the region with periods of 4-years and longer. One such fluctuation began in late 2002 and has been observed by the Gravity Recovery and Climate Experiment (GRACE). Even after accounting for possible ENSO-correlated variations, there is a significant trend in ocean bottom pressure in the region, equivalent to 0.7 ± 0.3 cm yr−1 of sea level from January 2003 until December 2008, which is confirmed with steric-corrected altimetry. Although this low-frequency fluctuation does not appear in the ocean model, we show that ECMWF winds have a significantly reduced trend that is inconsistent with satellite observations over the same time period, and so it appears that the difference is due to a forcing error in the model and not an intrinsic error.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Estimating Mean Sea Level Change from the TOPEX and Jason Altimeter Missions - R. S. Nerem; D. P. Chambers; C. Choe; G. T. Mitchum (Marine Geodesy, 2010)

Hox cluster duplication in the basal teleost Hiodon alosoides (Osteoglossomorpha) - Karen E. Chambers; Ryan McDaniell; Jeremy D. Raincrow; Maya Deshmukh; Peter F. Stadler; Chi-hua Chiu (Theory in Biosciences, 2009)

Surface and Subsurface Geostrophic Current Variability in the Indian Ocean from Altimetry - Dara D. H. Cadden; Bulusu Subrahmanyam; Don P. Chambers; V. S. N. Murty (Marine Geodesy, 2009)

BRMS1 suppresses breast cancer metastasis in multiple experimental models of metastasis by reducing solitary cell survival and inhibiting growth initiation - Benjamin D. Hedley; Kedar S. Vaidya; Pushar Phadke; Lisa MacKenzie; David W. Dales; Carl O. Postenka; Ian C. MacDonald; Ann F. Chambers (Clinical & Experimental Metastasis, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Recent vegetation history of Drygarn Fawr (Elenydd SSSI), Cambrian Mountains, Wales: implications for conservation management of degraded blanket mires - F. M. Chambers; D. Mauquoy; E. W. Cloutman; J. R. G. Daniell; P. S. Jones (Biodiversity and Conservation, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Taxonomic Considerations in Listing Subspecies Under the U.S. Endangered Species Act - SUSAN M. HAIG; ERIK A. BEEVER; STEVEN M. CHAMBERS; HOPE M. DRAHEIM; BRUCE D. DUGGER; SUSIE DUNHAM; ELISE ELLIOTT‐SMITH; JOSEPH B. FONTAINE; DYLAN C. KESLER; BRIAN J. KNAUS; IARA F. LOPES; PETE LOSCHL; et al. (Conservation Biology, 2006)
The U.S. Endangered Species Act (ESA) allows listing of subspecies and other groupings below the rank of species. This provides the U.S. Fish and Wildlife Service and the National Marine Fisheries Service with a means to target the most critical unit in need of conservation. Although roughly one‐quarter of listed taxa are subspecies, these management agencies are hindered by uncertainties about taxonomic standards during listing or delisting activities. In a review of taxonomic publications and societies, we found few subspecies lists and none that stated standardized criteria for determining subspecific taxa. Lack of criteria is attributed to a centuries‐old debate over species and subspecies concepts. Nevertheless, the critical need to resolve this debate for ESA listings led us to propose that minimal biological criteria to define disjunct subspecies (legally or taxonomically) should include the discreteness and significance criteria of distinct population segments (as defined under the ESA). Our subspecies criteria are in stark contrast to that proposed by supporters of the phylogenetic species concept and provide a clear distinction between species and subspecies. Efforts to eliminate or reduce ambiguity associated with subspecies‐level classifications will assist with ESA listing decisions. Thus, we urge professional taxonomic societies to publish and periodically update peer‐reviewed species and subspecies lists. This effort must be paralleled throughout the world for efficient taxonomic conservation to take place.

Molecular analysis of isolates from influenza B outbreaks in the U.S. and Nepal, 2005 - L. T. Daum; L. C. Canas; A. I. Klimov; M. W. Shaw; R. V. Gibbons; S. K. Shrestha; K. S. Myint; R. P. Acharya; N. Rimal; F. Reese; D. M. Niemeyer; B. P. Arulanandam; et al. (Archives of Virology, 2006)

Spatial Continuity of Tree Attributes in Bottomland Hardwood Forests in the Southeastern United States - Luben D. Dimov; Jim L. Chambers; Brian Roy Lockhart (Forest Science, 2005)
Sustainable forest management and conservation require understanding of underlying basic structural and competitive relationships. To gain insight into these relationships, we analyzed spatial continuity of tree basal area (BA) and crown projection area (CPA) on twelve 0.64-ha plots in four mixed bottomland hardwood stands in Louisiana, Arkansas, and Mississippi. Variogram range indicated that BA spatial continuity of trees with dbh >10.0 cm extended an average 4.5 m. This distance equaled the quadratic mean crown radius (QMCR) of the overstory trees. Overall, 95% of the variability in BA was accounted for by the spatially structured variance and could be modeled as spatial dependence. Removal of suppressed trees from the analyses reduced the variability in BA at small separation distances and increased the variogram range. The average spatial continuity of unsuppressed trees averaged 18.2 m and was 17.6, 18.5, and 18.5 m based on the BA variograms, CPA variograms, and cross-variograms, respectively. This distance corresponded to four times the QMCR of the overstory trees and extended far enough to encompass the first- and second-order neighbors. The results suggest an existence of complex competitive influences and confirm findings in nonwoody vegetation that competitive effects can propagate beyond the direct neighbors. FOR. SCI. 51(6):532–540.

GGM02 – An improved Earth gravity field model from GRACE - B. Tapley; J. Ries; S. Bettadpur; D. Chambers; M. Cheng; F. Condi; B. Gunter; Z. Kang; P. Nagel; R. Pastor; T. Pekker; S. Poole; et al. (Journal of Geodesy, 2005)

Tree allometry and improved estimation of carbon stocks and balance in tropical forests - J. Chave; C. Andalo; S. Brown; M. A. Cairns; J. Q. Chambers; D. Eamus; H. Fölster; F. Fromard; N. Higuchi; T. Kira; J.-P. Lescure; B. W. Nelson; et al. (Oecologia, 2005)

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Expression and evolutionary analysis of West Nile virus (Merion Strain) - Mathura P Ramanathan; Jerome A Chambers; Jesse Taylor; Bette T Korber; Mark D Lee; Aysegul Nalca; Kesan Dang; Panyupa Pankhong; Watcharee Attatippaholkun; David B Weiner (Journal of NeuroVirology, 2005)

Nitrogen uptake and turnover in riparian woody vegetation - Chris Chambers; John D. Marshall; Robert J. Danehy (Oecologia, 2004)

Assessment of antimicrobial activity of hydrophilic betaines in osmotically stressed bacteria. - Barbara A. Peddie; Jacqueline E. Wood; Michael Lever; D. Alan R. Happer; Frederick de Zwart; Stephen T. Chambers (Antonie van Leeuwenhoek, 2003)

Diverged evolution of recent equine-2 influenza (H3N8) viruses in the Western Hemisphere - A. C. K. Lai; T. M. Chambers; R. E. Holland, Jr.; P. S. Morley; D. M. Haines; H. G. G. Townsend; M. Barrandeguy (Archives of Virology, 2001)

Trends in extreme daily rainfall and temperature in Southeast Asia and the South Pacific: 1961–1998 - M.J. Manton; P.M. Della‐Marta; M.R. Haylock; K.J. Hennessy; N. Nicholls; L.E. Chambers; D.A. Collins; G. Daw; A. Finet; D. Gunawan; K. Inape; H. Isobe; et al. (International Journal of Climatology, 2001)
Trends in extreme daily temperature and rainfall have been analysed from 1961 to 1998 for Southeast Asia and the South Pacific. This 38‐year period was chosen to optimize data availability across the region. Using high‐quality data from 91 stations in 15 countries, significant increases were detected in the annual number of hot days and warm nights, with significant decreases in the annual number of cool days and cold nights. These trends in extreme temperatures showed considerable consistency across the region. Extreme rainfall trends were generally less spatially coherent than were those for extreme temperature. The number of rain days (with at least 2 mm of rain) has decreased significantly throughout Southeast Asia and the western and central South Pacific, but increased in the north of French Polynesia, in Fiji, and at some stations in Australia. The proportion of annual rainfall from extreme events has increased at a majority of stations. The frequency of extreme rainfall events has declined at most stations (but not significantly), although significant increases were detected in French Polynesia. Trends in the average intensity of the wettest rainfall events each year were generally weak and not significant. Copyright © 2001 Royal Meteorological Society

The interaction between water movement, sediment dynamics and submersed macrophytes - J. D. Madsen; P. A. Chambers; W. F. James; E. W. Koch; D. F. Westlake (Hydrobiologia, 2001)

Land–atmosphere energy exchange in Arctic tundra and boreal forest: available data and feedbacks to climate - Werner Eugster; Wayne R Rouse; Roger A. Pielke Sr; Joseph P. Mcfadden; Dennis D Baldocchi; Timothy G. F Kittel; F. Stuart Chapin; Glen E. Liston; Pier Luigi Vidale; Eugene Vaganov; Scott Chambers (Global Change Biology, 2000)
Summary This paper summarizes and analyses available data on the surface energy balance of Arctic tundra and boreal forest. The complex interactions between ecosystems and their surface energy balance are also examined, including climatically induced shifts in ecosystem type that might amplify or reduce the effects of potential climatic change. High latitudes are characterized by large annual changes in solar input. Albedo decreases strongly from winter, when the surface is snow‐covered, to summer, especially in nonforested regions such as Arctic tundra and boreal wetlands. Evapotranspiration ( Q E ) of high‐latitude ecosystems is less than from a freely evaporating surface and decreases late in the season, when soil moisture declines, indicating stomatal control over Q E , particularly in evergreen forests. Evergreen conifer forests have a canopy conductance half that of deciduous forests and consequently lower Q E and higher sensible heat flux ( Q H ). There is a broad overlap in energy partitioning between Arctic and boreal ecosystems, although Arctic ecosystems and light taiga generally have higher ground heat flux because there is less leaf and stem area to shade the ground surface, and the thermal gradient from the surface to permafrost is steeper. Permafrost creates a strong heat sink in summer that reduces surface temperature and therefore heat flux to the atmosphere. Loss of permafrost would therefore amplify climatic warming. If warming caused an increase in productivity and leaf area, or fire caused a shift from evergreen to deciduous forest, this would increase Q E and reduce Q H . Potential future shifts in vegetation would have varying climate feedbacks, with largest effects caused by shifts from boreal conifer to shrubland or deciduous forest (or vice versa) and from Arctic coastal to wet tundra. An increase of logging activity in the boreal forests appears to reduce Q E by roughly 50% with little change in Q H , while the ground heat flux is strongly enhanced.

Seasonal sea level change from TOPEX/Poseidon observation and thermal contribution - J. L. Chen; C. K. Shum; C. R. Wilson; D. P. Chambers; B. D. Tapley (Journal of Geodesy, 2000)

Detection of Legionella DNA in Guinea Pig Peripheral Leukocytes, Urine and Plasma by the Polymerase Chain Reaction - L. C. Jennings; S. T. Chambers; D. R. Murdoch; G. J. Light (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Adaptation and serial passage of porcine group C rotavirus in ST-cells, an established diploid swine testicular cell line - M. W. Welter; C. J. Welter; D. M. Chambers; L. Svensson (Archives of Virology, 1991)

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

Short-term interactions between DDT and endrin accumulation and elimination in mosquitofish (Gambusia affinis) - Michael S. Denison; Janice E. Chambers; James D. Yarbrough (Archives of Environmental Contamination and Toxicology, 1985)

Effects of parasite density and host availability on progeny production byBiosteres (Opius) longicaudatus, [Hym.: Braconidae], a parasite ofAnastrepha suspensa [Dip.: Tephritidae] - T. R. Ashley; D. L. Chambers (BioControl, 1979)

Comparative life history and respiratory activity of “wild” and colonized Caribbean fruit flies [Dipt.: Tephritidae] - N. C. Leppla; M. D. Huettel; D. L. Chambers; W. K. Turner (BioControl, 1976)

Rearing and life history studies onBiosteres (Opius) longicaudatus [Hym.: Braconidae] - P. D. Greany; T. R. Ashley; R. M. Baranowski; D. L. Chambers (BioControl, 1976)

An inhalational toxicity study with dichlorvos - A. I. T. Walker; D. Blair; D. E. Stevenson; P. L. Chambers (Archives of Toxicology, 1972)

Toxicological studies with the herbicide 2,6-dichloro-thiobenzamide (chlorthiamid, ?Prefix?) - V. K. H. Brown; P. L. Chambers; L. W. Ferrigan; D. E. Stevenson; D. A. Williams (Archives of Toxicology, 1967)